Significant Relationship between Hypertension and Obesity among Female Patients at A Hospital in Kupang, Indonesia - Darlene Monica Wijaya; Desi Indriarini; Herman Pieter Louis Wungouw; I Made Artawan (Althea Medical Journal)
Background: Hypertension or high blood pressure is one of the most common non-communicable diseases found nowadays, affecting 1.28 billion people worldwide and causing about 7.5 million deaths annually. Many factors contribute to hypertension, one of which is obesity. This study aimed to explore further the relationship between hypertension and obesity, especially in female patients in Kupang, Indonesia.